Use of Image Processing Techniques for Making Run out Decision in Cricket (International Journal of Engineering and Computer Science, 2017)
In the world renowned game of Cricket, currently for giving umpiring decisions like Stumping and Run Out, the Third Umpire has to review the various angular video footages thoroughly and laboriously. According to the current Laws of Cricket, the Third Umpire is expected to give the correct decision within 30 seconds, although it’s in his discretion to take as much time required by him. This process evidently takes a lot more time than 30 seconds. Hence, a software system for assisting the Third Umpire, is required that will helpcut short the above time lag. Then, the Third Umpire will just provide the Video feeds as input to the system and it will compute a result, which will aid the Third Umpire in reaching a decision quickly. Our Idea is to use Image Processing techniques which can provide us with the means of building such a software system that can be used for the above mentioned scenario. The Software system will make use of Object tracking algorithm for tracking Wickets, and depending on the displacement of wickets the frames of that moment will be taken using a Frame Extraction algorithm